Positive Findings of Blood Cultures in Febrile Children Presenting with Thalassemia Major in a Tertiary Care Hospital - Itrat Fatima; Wafia Affan; Hira Hameed; Wajeeha Amber; Sumbal Saeed; Imran Mahmood Khan (Journal of Rawalpindi Medical College)
Objective: To assess status of bacterial pathogens in thalassemia major patients presenting with fever in a tertiary care hospital